1998
DOI: 10.1073/pnas.95.8.4419
|View full text |Cite
|
Sign up to set email alerts
|

Polyploid formation created unique avenues for response to selection in Gossypium (cotton)

Abstract: A detailed restriction fragment length polymorphism map was used to determine the chromosomal locations and subgenomic distributions of quantitative trait loci (QTLs) segregating in a cross between cultivars of allotetraploid (AADD) Gossypium hirsutum (''Upland'' cotton) and Gossypium barbadense (''Sea Island,'' ''Pima,'' or ''Egyptian'' cotton) that differ markedly in the quality and quantity of seed epidermal fibers. Most QTLs inf luencing fiber quality and yield are located on the ''D'' subgenome, derived f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
249
0
6

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 318 publications
(272 citation statements)
references
References 42 publications
17
249
0
6
Order By: Relevance
“…All DR gene copies lost from tetraploid species in this study were from the D genome (DRs 4 and 28; Figures 1b, e, and 3). Further, for both DR genes and randomly selected genes, most homoeologous restriction site mutations occurred in the D genome (Figures 1 and 3), in accordance with the discovery of more DNA-level variations in the D than the A genome (Reinisch et al, 1994;Jiang et al, 1998;Small and Wendel, 2002;Grover et al, 2007). More DNA-level variation found in the D genome than the A genome may be symptomatic of mechanisms that also contribute to the greater abundance of QTLs responsible for phenotypic variation, including fiber-related QTLs detected on this genome from a nonfiber-producing ancestor (Jiang et al, 1998;Rong et al, 2007).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…All DR gene copies lost from tetraploid species in this study were from the D genome (DRs 4 and 28; Figures 1b, e, and 3). Further, for both DR genes and randomly selected genes, most homoeologous restriction site mutations occurred in the D genome (Figures 1 and 3), in accordance with the discovery of more DNA-level variations in the D than the A genome (Reinisch et al, 1994;Jiang et al, 1998;Small and Wendel, 2002;Grover et al, 2007). More DNA-level variation found in the D genome than the A genome may be symptomatic of mechanisms that also contribute to the greater abundance of QTLs responsible for phenotypic variation, including fiber-related QTLs detected on this genome from a nonfiber-producing ancestor (Jiang et al, 1998;Rong et al, 2007).…”
Section: Discussionmentioning
confidence: 69%
“…Other investigators also found fiber-related cDNA/genes to show more copies in G. raimondii than in diploid A genome species (Orford et al, 1999;Orford and Timmis, 2000). The possibility that G. raimondii may have slightly higher gene copy numbers than A genome species might contribute to recurring reports of a slightly higher level of DNA polymorphism in the D genome than that can be detected in A genome (Reinisch et al, 1994;Jiang et al, 1998;Small and Wendel, 2002;Grover et al, 2007). All DR gene copies lost from tetraploid species in this study were from the D genome (DRs 4 and 28; Figures 1b, e, and 3).…”
Section: Discussionmentioning
confidence: 94%
“…Here we found many common characteristics of QTLs related to fiber quality traits as described in the previous reports involving interspecific maps [3,10,23,[33][34][35][36][37][38] and intraspecific maps [12,15,26,30,[39][40][41][42][43][44][45][46], although few common markers were used in the present research and the previous studies, and the maps covered different region parts of cotton genome, making it difficult to compare the common QTLs, some QTLs were detected and mapped on the same chromosomes and affect common traits. These include seven QTLs for fiber length located in the same chromosomal regions as reported earlier [10,26,34,41,42], two QTLs for fiber uniformity ratio located in the same chromosomal regions [43,46], two QTLs for fiber micronaire [10,43,44], three QTLs for fiber elongation [30,36,42,43,46,47], and 4 QTLs for fiber strength [26,34,36,43,44,46,47].…”
Section: Qtls For Cotton Fiber Quality Traitsmentioning
confidence: 66%
“…Polyploidy often confers emergent properties, such as the higher fibre productivity and quality of tetraploid cottons than diploid cottons bred for the same environments 1 . Here we show that an abrupt five-to sixfold ploidy increase approximately 60 million years (Myr) ago, and allopolyploidy reuniting divergent Gossypium genomes approximately 1-2 Myr ago 2 , conferred about 30-36-fold duplication of ancestral angiosperm (flowering plant) genes in elite cottons (Gossypium hirsutum and Gossypium barbadense), genetic complexity equalled only by Brassica 3 among sequenced angiosperms.…”
mentioning
confidence: 99%